1989
DOI: 10.1111/j.1528-1157.1989.tb05471.x
|View full text |Cite
|
Sign up to set email alerts
|

Relief of Seizures from a Predominantly Posterior Temporal Tumor with Anterior Temporal Lobectomy

Abstract: We report the relief of intractable complex partial seizures in a patient with a posteromesial temporal lobe hamartoma after anterior temporal lobectomy, despite minimal tumor removal. We suggest that the key to successful treatment is the mainly medial, or limbic, location of the tumor, which apparently requires anterior limbic structures for full clinical expression of seizures. We conclude that excision anterior to a posterior temporal lesion can result in seizure relief and that a medial tumor location may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 10 publications
1
13
0
2
Order By: Relevance
“…Noninvasive recording and careful mapping show that a structural lesion is not the source of epileptic activity (12)(13)(14). Some studies about lesional epilepsies showed lateralization of epileptogenic foci to distant ipsilateral (15,16) or even to contralateral regions (17). However, few studies have addressed a clear correlation between the lesion site and epileptogenic foci of the ictal onset zone as well as the irritative zone.…”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive recording and careful mapping show that a structural lesion is not the source of epileptic activity (12)(13)(14). Some studies about lesional epilepsies showed lateralization of epileptogenic foci to distant ipsilateral (15,16) or even to contralateral regions (17). However, few studies have addressed a clear correlation between the lesion site and epileptogenic foci of the ictal onset zone as well as the irritative zone.…”
Section: Introductionmentioning
confidence: 99%
“…Clear guidelines of surgery for LTLE were absent, and seizure reduction or cure by anterior temporal lobectomy in remote posterior lesion was reported in several studies 9,10. We included the anterior temporal area because of the rapid propagation of ictal rhythms from the posterior to anterior temporal area.…”
Section: Discussionmentioning
confidence: 99%
“…This tendency is seen from the fact that lesionectomy alone relieved seizures in 9 of 14 patients with extra temporal lesions, but in only 2 out of 9 patients with temporal lesions 6 . It is possible that secondary foci develop more often, and become autonomous more readily in the temporal lobes than in other areas of the brain 16 -42 - 45 . Whether GGs abet this process, or whether their association is merely a statistical illusion, needs to be looked into.…”
Section: Discussionmentioning
confidence: 99%